Calcul De L’esperance De Vie Des Chomeurs En Rrepublique Democratique Congo/Kinshasa (2021-2022) Par La Methode De Regression Logistique Binaire Floue. - Delagrave, Kapata Nawej Tshisunz Hedrezy; Laka Jose, Idenge Yes’sambala; Rostin, Mabela Makengo; Benjamin, Boono Yaba (International Journal of Scientific Research and Management (IJSRM), 2025)
The main objective of this research was to contribute to the empirical literature on the application of fuzzy binary logistic regression to the life expectancy of the unemployed in DRC/Kinshasa. Specifically, it aimed to evaluate the proportion of households living without employment (unemployed), identify the explanatory or determining factors of the life expectancy of the unemployed, and finally determine the effects of factors directly related to household living conditions.The data for this study were collected through a survey of 386 households in Kinshasa, selected using a non-probabilistic sampling method. Descriptive statistics, inferential statistics, and multiple regression based on the logistic model were used to identify the explanatory factors of the life expectancy of the unemployed.The results of this study reveal that most of the surveyed households are unemployed (92.49%). Logistic regression reveals that the explanatory factors that improve the life expectancy of the unemployed in Kinshasa are: level of education (secondary and graduate), parcel occupation status (owner), activity characteristics (informal), time allocated to informal activities, prioritized healthcare mode (modern medicine), income (medium and high), and access to drinking water. On the other hand, the factors that reduce the life expectancy of the unemployed are: low income and non-food expenditure (medium).